Histological Characterization and Immunohistochemical Localization of Ki-67 and VEGF Factors in Bitches' Corpus Luteum at Cyclic and Early and Late Gestational Diestrous - Ribeiro, A. A. [UNESP]; Martin, I. [UNESP]; Derussi, A. A. P. [UNESP]; Ferioli, R. B. [UNESP]; Laufer-Amorim, R. [UNESP]; Lopes, Maria Denise [UNESP] (Wiley-Blackwell, 2012)
Contents The luteal phase on pregnant and non-pregnant bitches is characteristic of this species and resembles significantly with respect to the growth pattern and luteal regression. Histological and immunostaining studies of the corpus luteum (CL) may help to elucidate differences between the CL of pregnant and non-pregnant bitches. The purpose of this study was to characterize histologically and localize by immunohistochemistry the cell proliferation (Ki-67) and vascular endothelial growth (VEGF) factors in the CL of pregnant and non-pregnant bitches. Eighteen bitches were analysed and distributed into three groups: In group I (gestational diestrous), seven bitches were subjected to two inseminations at 4 and 6 days after the pre-ovulatory LH surge and ovariohysterectomized (OSH) at 821 days after the first insemination. In group II (cyclic diestrous; control), 6 (Ki-67) or 8 (VEGF) bitches that were determined as non-pregnant were OSH at 1225 days of the pre-ovulatory LH surge. In group III (late pregnancy), three bitches had their ovary removed during caesarean section at 6264 days after the pre-ovulatory LH surge. Portions of the ovarian cortex containing CLs were cut and stored for histological and immunohistochemical analysis. Histological evaluation of the ovarian cortex showed a marked similarity in the morphological pattern among the CLs in all three groups. The morphology and expression pattern of VEGF and Ki-67 factors in CLs of cyclic and gestational diestrous bitches were similar but significantly lower than that of late pregnant bitches (p < 0.05).